Self-fulfilling debt dilution : maturity and non-existence of equilibrium in debt models - Chizzotti, José Mario (2022)
In this dissertation I show that in models of long-term sovereign debt, lenders’ expectations of future bond prices and the country’s future borrowing behaviour can be self-fulfilling, leading to multiple equilibria, or they can be inconsistent with the incentives they provide to the country, in which case no Markov equilibrium in pure strategies exist. Both the possibility of non-existence of equilibrium and equilibrium multiplicity steams from the feedback between equilibrium bond prices, which embed a expected future borrowing behaviour, and the current and future optimal level of borrowing by the country. The inability of the country to commit to a certain level of future borrowing is also crucial for those results. In the models I analyse, what determines whether the equilibrium exists or whether it is unique is essentially the function for the direct cost of default and the extent of the maturity of debt contracts.